Helmintos de la República de Costa Rica XIX. Nematoda 5. Algunos nemátodos parásitos de Gallus gallus domesticus (L) - Brenes, Rodrigo Ramón (1962)
Three species of nematodes, CaPillaria obsignata Madsen, 1945; OxysPimra (Yorkeispirura) mansoni (Cobbold, 1879) (Skrjabin, 1931 ); and Tetrameres fissispina (Diesing, 1861) Travassos, 1914, parasitic on domestic fowl, are redescribed from Costa - Rican material. The intermediate host of OxysPirura mansoni Pycnoscelus surinamensis L. was found naturally infected. Experimental infection was made in chickens, coves and the wood duck Dendrocygna a. autumnalis; adult parasites were found in the nasolacrymal ducts and nyctitant membranes, and eggs and first stage larvae in the feces.